Coordination‐Induced Spin‐State Switching with Nickel(II) salpn Complexes: Electronic versus Steric Effects and Influence of Intermolecular Interactions. Issue 5 (29th January 2018) - Brandenburg, Hannah; Krahmer, Jan; Fischer, Kim; Schwager, Bettina; Flöser, Benedikt; Näther, Christian; Tuczek, Felix
Abstract : Four nickel(II) salpn (salicylidenepropylene iminate) complexes are investigated concerning their capability to perform CISSS (coordination‐induced spin‐state switching). To this end, pyridine titration experiments are performed with the nickel salpn complexes [Ni(salpn)], [Ni(salpn t BuCF3 )], [Ni(salpnCF3 )] and [Ni(salpnSbenz)]. The electronic‐structural changes are monitored by UV/Vis spectroscopy and Evans NMR spectroscopy. Association constants ( K 1s and K 2 ), as well as thermodynamic parameters (Δ H, Δ S, and Δ G ), for the binding of pyridine are determined. In comparison with porphyrins and porphyrin‐derived systems investigated earlier, the salpn systems exhibit quite different coordination properties. In particular, the fluorinated systems show the formation of dimers due to CH–π and π–π stacking. On the other hand, the investigated compounds coordinate axial ligands with affinities comparable with those of the porphyrin‐based analogs. This renders them eligible for the preparation of LD‐CISSS (light‐driven CISSS) systems, which, in turn, may be applied as functional MRI contrast agents. Abstract : Four nickel(II) salpn (salicylidenepropylene iminate) complexes are investigated for potential use in CISSS (coordination‐induced spin‐state switching). Pyridine titration experiments are performed; thermodynamic parameters for pyridine binding are comparable with those of porphyrin‐based analogs. Thus, the new complexes are eligible for the synthesis of LD‐CISSS (light‐driven CISSS) systems.